Leaf Anatomy of Three Varians of Arundina graminifolia (D. Don.) Hochr - Sulistiarini, Diah; Tihurua, Eka Fatmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
Three variations of Arundina graminifolia flowers have been recognized, (1) group of big flower with reddish violetlip and purplelish white sepals and petals (2) group of small flower with white lip and white sepals and petals (3)similar to second variation but with purple color on the lip apex. In order to clarify the taxonomy status of thosethree variations, a leaf anatomical study had been carried out. Results of this study showed that there were somedifferences among them in trichome shape and number mesophyll layers. Big flower group of Arundina hastrichome club shape and thick mucous in the apex with mesophyll layer 9-11; for small flower group has white lip,trichome club shape, thick mucous and granulate in the apex, but only 2 mesophyl layers; whereas for other smallflower group with purple lip has trichome cup shape and 10-13 layers of mesophyll. Based on the differences inflower size and their color variation, and combined with leaf anatomical study, we suggested the three variationsof A. graminifolia should be in separated groups.